2014
DOI: 10.1371/journal.pntd.0002958
|View full text |Cite
|
Sign up to set email alerts
|

High Reinfection Rate after Preventive Chemotherapy for Fishborne Zoonotic Trematodes in Vietnam

Abstract: BackgroundThe World Health Organization aims for complete morbidity control of fishborne zoonotic trematodes (FZT) in endemic areas by 2020. The main intervention tool for achieving this goal is regular use of preventive chemotherapy by offering praziquantel to those at risk in endemic areas. The purpose of this study was to investigate the effectiveness of preventive chemotherapy to control FZT in an endemic area in Northern Vietnam.Methodology and principle findingsWe followed a cohort of 396 people who fulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The association between frequent PZQ treatment and re-infection has also been shown in other studies of the liver fluke [ 18 , 20 ]. This pattern of infection and re-infection after treatment has also been found in Vietnam [ 26 ]. Another study in Laos found no significant association between past PZQ treatment and infection [ 27 ], however, this study only measured whether the medication had ever been taken, not the frequency of previous treatments.…”
Section: Discussionsupporting
confidence: 74%
“…The association between frequent PZQ treatment and re-infection has also been shown in other studies of the liver fluke [ 18 , 20 ]. This pattern of infection and re-infection after treatment has also been found in Vietnam [ 26 ]. Another study in Laos found no significant association between past PZQ treatment and infection [ 27 ], however, this study only measured whether the medication had ever been taken, not the frequency of previous treatments.…”
Section: Discussionsupporting
confidence: 74%
“…As individuals previous infected with C. sinensis show no apparent protective immunity after recovery from treatment [27] and re-infection is common in endemic areas [9,28], we proposed a deterministic Susceptible-Infected-Susceptible (SIS) model to describe the transmission of C. sinensis among human-snail-fish populations, where infected human recovered from infection will instantly return to the susceptible state. According to different frequencies of raw-fish consumption, we classified the human population into four groups, that is seldom, moderately (less than 5 times per year), often (5-10 times per year) and very often (more than 10 times per year) eating of raw fish.…”
Section: The Basic Modelmentioning
confidence: 99%
“…Based on a typical setting of C. sinensis transmission (Fusha Town), we simulated scenarios according to strategies recommended by WHO, the Chinese government and the government of Guangdong Province, with intervention duration of five years. On one hand, the WHO strategy, mainly focusing on chemotherapy of whole population, could decrease the human prevalence rapidly but were not sustainable (Fig 4), even with an extension of intervention duration to 30 years (S4 Fig), which may due to the high reinfection of the disease [9,28]. On the other hand, strategies recommended by the Chinese government and the government of Guangdong Province could reach their setting goals within 5 years of intervention (Fig 4).…”
Section: Three Recommended Strategiesmentioning
confidence: 99%
“…As NTDs have garnered much-needed attention in recent years, many global partnerships have been formed and several pharmaceutical companies have pledged free drugs to combat NTDs worldwide [ 4 ]. Preventive chemotherapy has been shown to be effective in reducing the prevalence and morbidity of NTDs but reinfection with the parasite is also very common among endemic populations [ 5 7 ].…”
Section: Main Textmentioning
confidence: 99%
“…More often than not, interventions were treatment-oriented and solely aimed at alleviating the current complication that were plaguing the target population. For instance, although preventive chemotherapy by means of mass drug administration (MDA) could bring down the prevalence, the reinfection rate is also high [ 5 7 ]. This intervention through MDA alone brings the issue of sustainability into question.…”
Section: Main Textmentioning
confidence: 99%